2019
DOI: 10.3389/fnbeh.2019.00159
|View full text |Cite
|
Sign up to set email alerts
|

Varenicline Targets the Reinforcing-Enhancing Effect of Nicotine on Its Associated Salient Cue During Nicotine Self-administration in the Rat

Abstract: Nicotine is acknowledged as the key addictive compound of tobacco. Varenicline (Champix ® or Chantix ® ), mainly acting as a partial agonist at the α4β2 nicotinic receptor, is an approved smoking cessation pharmacotherapy, although with efficacy limited to a portion of smokers. Smokers differ in the motives that drive their drug seeking and Varenicline might be more efficient in some groups more than others. Studies in rodents revealed that nicotine-seeking is stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
2
3
0
Order By: Relevance
“…Our data support this: at a population level, varenicline can moderately enhance cue reinforcing effects in rats self-administering i.v. saline+cue (Fig5b), and antagonize nicotine-induced enhancement of cue reinforcing effects (FigS4k-l), in accordance with a previous study done in our laboratory (30). Critically, our self-administration data also reveal that the behavioral effects of varenicline in the absence of nicotine can be different, or even opposed, depending on the individual psychopharmacological profile of nicotine-cue interactions: varenicline decreases cue self-administration in cluster B, but slightly increased it in cluster A (Fig 5a-b), consistent with the observed effect in reinforcement enhancement (Fig5b).…”
Section: Varenicline Can Have Different Behavioral Outcomes In the Absence Of Nicotine Depending On The Individual Psychopharmacological supporting
confidence: 92%
See 1 more Smart Citation
“…Our data support this: at a population level, varenicline can moderately enhance cue reinforcing effects in rats self-administering i.v. saline+cue (Fig5b), and antagonize nicotine-induced enhancement of cue reinforcing effects (FigS4k-l), in accordance with a previous study done in our laboratory (30). Critically, our self-administration data also reveal that the behavioral effects of varenicline in the absence of nicotine can be different, or even opposed, depending on the individual psychopharmacological profile of nicotine-cue interactions: varenicline decreases cue self-administration in cluster B, but slightly increased it in cluster A (Fig 5a-b), consistent with the observed effect in reinforcement enhancement (Fig5b).…”
Section: Varenicline Can Have Different Behavioral Outcomes In the Absence Of Nicotine Depending On The Individual Psychopharmacological supporting
confidence: 92%
“…The classical, and most widely used, preclinical model of nicotine intravenous self-administration in the rat involves the contingent delivery of nicotine with a visual stimulus ('cue') (28). We and others have shown that this type of visual stimuli is not neutral, but drives self-administration behavior by itself, working as a mild primary reinforcer (22,(29)(30)(31)(32). Hence, the two types of psychopharmacological interactions between the nicotine and the visual cue can contribute to nicotine+cue selfadministration.…”
Section: Introductionmentioning
confidence: 99%
“…However their active lever pressing was maintained significantly higher than the inactive lever responding and reinstated to baseline during cue-reinforced responding under extinction conditions. Other previous studies have confirmed the contribution of environmental cues in driving self-administration behavior, that when paired with contingent saline-SA produced even stronger responding than nicotine-SA in the absence of these stimuli ( Donny et al, 2003 ; Garcia-Rivas et al, 2019 ). However, this mild reinforcing effect of visual cues in driving operant behavior did not produce any sustained neuroadaptations in the saline-SA group when compared to yoked-treated control within the accumbens shell.…”
Section: Discussionsupporting
confidence: 59%
“…Conversely, a saline self-administering group can be used to control for neurophysiological transformations that may be shielded by neuroadaptations produced when conditioned visual cues are associated with operant responding. As a matter of fact, saline self-administering rats that respond for nicotine associated visual cues, present a stimulus-driven operant learning and are able to discriminate between active (rewarded) and inactive (non-rewarded) responses ( Donny et al, 2003 ; Garcia-Rivas et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, those individuals who are particularly vulnerable to tobacco cue-induced craving and relapse may benefit most from interventions that are likely to reduce nicotine reinforcement strength such as the nicotinic partial agonist, varenicline. Indeed, varenicline pre-treatment in rats reduces responding for nicotine under a PR schedule (Le Foll et al, 2012), has been shown to antagonise both the primary reinforcing effects of nicotine and the reinforcement-enhancing effect of nicotine on cues (Garcia-Rivas et al, 2019) and reduces cue reactivity (Franklin et al, 2011). Future research could ascertain if varenicline has greatest efficacy among smokers with the largest cue-reactivity.…”
Section: Discussionmentioning
confidence: 99%